Effect of swirl distortion on gas turbine operability - Mehdi, Ahad (Cranfield University, 2014)
The aerodynamic integration of an aero-engine intake system with the airframe can pose some notable challenges. This is particularly so for many military air- craft and is likely to become a more pressing issue for both new military systems with highly embedded engines as well as for novel civil aircraft configurations. During the late 1960s with the advent of turbo-fan engines, industry became in- creasingly aware of issues which arise due to inlet total pressure distortion. Since then, inlet-engine compatibility assessments have become a key aspect of any new development. In addition to total temperature and total pressure distortions, flow angularity and the associated swirl distortion are also known to be of notable con- cern. The importance of developing a rigorous methodology to understand the effects of swirl distortion on turbo-machinery has also become one of the major concerns of current design programmes. The goal of this doctoral research was to further the current knowledge on swirl distortion, and its adverse effects on engine performance, focusing on the turbo-machinery components (i.e. fans or compressors). This was achieved by looking into appropriate swirl flow descriptors and by correlating them against the compressor performance parameters (e.g loss in stability pressure ratios). To that end, a number of high-fidelity three-dimensional Computational Fluid Dynamics (CFD) models have been developed using two sets of transonic rotors (i.e. NASA Rotor 67 and 37), and a stator (NASA Stator 67B). For the numerical purpose, a boundary condition methodology for the definition of swirl distortion patterns at the inlet has been developed. Various swirl distortion numerical parametric studies have been performed using the modelled rotor configurations. Two types of swirl distortion pattern were investigated in the research, i.e. the pure bulk swirl and the tightly-wound vortex. Numerical simulations suggested that the vortex core location, polarity, size and strength greatly affect the compressor performance. The bulk swirl simula- tions also showed the dependency on swirl strength and polarity. This empha- sized the importance of quantifying these swirl components in the flow distortion descriptors. For this, a methodology have been developed for the inlet-engine compatibility assessment using different types of flow descriptors. A number of correlations have been proposed for the two types of swirl distortion investigated in the study.
Keywords: Bulk swirl; CFD; flow descriptors; Rotor 37; Rotor 67; Stator 67B; swirl distortion; tightly-wound vortex; turbo-machinery